PENINGKATAN PEMAHAMAN KONSEP BILANGAN MELALUI BERMAIN ANGKLUNG - Firsty, Dini Nurmalina; H, Myrnawati C; Hapidin, Hapidin (PEDAGOGIA, 2017)
The purpose of this study is to describe the process and results of angklung play activities to improveunderstanding of the concept of children under five in early childhood and whether angklung play can improveunderstanding of the concept of children in early childhood in 2017. Respondents in this study were 18 childrenfrom the group B PAUD Alfani in2017. The research method used is a model of Kemmis Taggart spiral actionresearch consisting of: (a) planning, (b) action and observation, and (c) reflection. Instruments used in this studyare field notes, interviews, and documentation. Scores of understanding data on economic concepts in children areanalyzed quantitatively and qualitatively. The result of the data shows that the concept of learning in childrenincreases from pre-cycle to first cycle and second cycle. Based on the observation of the action that has been doneon the data given at the incidence rate 40.09%, and in the first cycle to 59.41% and then increased in the secondcycle of 85.61%. The results of this study are (1) angklung playing activities can improve concept understanding inchildren group B PAUD Alfani in 2017, (2) concept comprehension score in children group B PAUD Alfani year2017 increase from pre cycle to first cycle and first cycle to second cycle